Effect of Laser Surface Treatment on Physical Properties of Composite Material (Al-B4C) - Selman, Khansaa; Mahmood, Sabah; Mohameed, Qamar (Iraqi Journal of Science, 2024)
This work study the effect of laser surface heat treatment on physical properties (green density, density after sintering, theoretical density and porosity)of a composite material of an Al powder as a matrix with different percentage of B4C powder as additive material. This work was done by two stages: First stage: Production the maincomposite material which is contain Al powder with grain size 24μm as a matrix and B4C powder with grain size 50μm as additive with different weight percentage (5%,10%,15%,20%,25%,30%), and the powders Maxined for suitable time 15min, after that the mixture compacted with 2ton and sintered at 550C0. Second stage: Laser surface treatment was done for the productive composite material after sintering by using pulse Nd: YAG laser with 1J energy, wave length 1064nm and pulse duration 100ns.Laser surface heat treatment was carried out with one pulse and two pulses respectively. Macrohardness of the composite material was measured after the sintering process and after the laser surface heat treatment with one pulse and two pulses, also photo-micrographies were taken for the specimens by using ordinary microscopic after each of sintering process and laser surface heat treatment. The results show that improvement of physical properties mentioned above and macrohardness after laser surface treatment with two pulses more than one pulse.